Pengenalan Virus Dan Bakteri Bagi Anak Usia Dini Untuk Pencegahan Penularan Penyakit - Henny Helmi; Eni Karsiningsih (ABDIPRAJA (Jurnal Pengabdian kepada Masyarakat), 2022)
Early childhood with the age of around 0-7 years is a phase in human life that is susceptible to various infectious diseases by bacteria and viruses. The incidence of infection in early childhood is due to an immature immune system. One of the efforts to prevent infection and disease transmission in early childhood is by educating children, in schools providing early childhood education. PAUD and Daycare Rumah Pelangi is one of the PAUD and Daycare in Pangkalpinang city which has 41 students and has been a partner for parents to educate their children since 2017. The purpose of this activity is to provide education to children in PAUD and Daycare Pelangi Pangkalpinang regarding the introduction of bacteria and viruses as well as efforts to prevent disease transmission. In this activity the methods of discussion, mentoring, and storytelling through animated videos were applied to children to facilitate understanding of bacteria and viruses. In this activity, PAUD students were educated on the shape and nature of bacteria and viruses, the effects caused by bacteria and viruses and how to prevent the transmission of diseases caused by viruses and bacteria. The results of this study indicate an increase in children's ability to wash their hands properly, knowledge of children regarding viruses and bacteria increases and the emergence of good habits in children to always use masks.